Experimental Study on Delayed Cell Death After Thawing and the Effect of Cryoprotective Base Solutions - Ho, YongIl; Mun, JongHyong; Pyo, KumChon; Pak, NamIl; Choi, SongGuk; Kang, Chol; Li, Chol; Lim , GyongMan; Choi, YongDo (Universitas Islam Negeri Ar-Raniry, 2026)
BACKGROUND: Cryopreservation is a cornerstone technology in regenerative medicine, cell therapy, and biobanking; however, delayed cell death (DCD) occurring 24–48 hours post-thaw remains a critical barrier to maintaining high-quality viable cells—even when immediate post-thaw viability exceeds 95%. OBJECTIVE: To investigate the occurrence of delayed cell death (DCD) in cells after thawing following cryopreservation, and to evaluate the regulatory effect of different cryoprotective base solutions, with a focus on establishing a UW solution-based cryopreservation protocol. MATERIALS AND METHODS: Six cell lines (PESUN, Vero, RD, RK13, VeroE6, L20B) were used to compare two freezing methods (rapid freezing vs. slow freezing) and two cryoprotective base solutions (DMEM vs. UW solution). Cell viability was detected by trypan blue staining, apoptotic cells by Giemsa staining, and cell biological characteristics (proliferation, viral susceptibility) were assessed. RESULTS: 1) DCD peaked at 24 h post-thaw: the mortality rate was 42.2% and apoptotic rate was 28.9% in DMEM-based groups. 2) UW solution (intracellular-type, low Na⁺/high K⁺) significantly reduced DCD: 24 h post-thaw mortality was 21.8% (vs. 43.2% in DMEM) and apoptotic rate was 13.9% (vs. 28.9% in DMEM, both P<0.05). 3) The optimal UW-based protocol was confirmed as: 20% dimethyl sulfoxide (DMSO), 1 min room temperature equilibration, rapid freezing, 37°C water bath thawing, 2.5% glucose in dilution medium, and ≥4-fold dilution. 4) Cells preserved by this protocol maintained pre-cryopreservation properties (proliferation index: 3.27 vs. 3.23; doubling time: 41.8 h vs. 42.2 h; Echovirus B1 log₁₀ TCID₅₀/mL: 7.50 vs. 7.50). CONCLUSION: Post-thaw DCD is closely associated with apoptosis. The UW solution-based cryopreservation protocol effectively reduces DCD while preserving cell function, providing a reliable strategy for clinical cell cryopreservation.